Effect of drought stress on physiological behavior and growth ofblack locust (Robinia pseudoacacia) seedlings - Novita Anggraini; Eny Faridah; Sapto Indrioko (Jurnal Ilmu Kehutanan)
Black locust (Robinia pseudoacacia) is a native species from North America and it has spread to Europe and Asia. Black locust is also one species used for land rehabilitation in semiarid and arid areas. However, adaptability of black locust on their distribution area is quite disturbing due to its invasive potential that tends to suppress the growth of native plants. The purpose of this study is to examine the effect of drought stress through watering volume and watering intervals treatments on physiological behavior and growth of black locust seedlings, and to analyze the level of black locust on drought tolerance through water use efficiency (WUE) character and chlorophyll content. The watering volumes are 30-40 % of field capacity representing drought conditions and 70-80 % of field capacity representing good water conditions, while the watering intervals are 1, 3 and 7 days. Trend analysis is used to analyze the data. The results indicate that the lower watering volume (30-40 %) and the longer the watering interval (for 7 days), the lower the photosynthesis and transpiration rate, stomatal conductance and growth (height, diameter, shoot dry weight and root) of plants, but the higher the WUE and chlorophyll content. Increasing WUE and chlorophyll content are two indicators indicating that black locust is able to adapt (tolerant) to drought stress situations. Therefore, the use of black locust for dry land reclamation requires special attention and careful strategy to avoid its invasive impact in the future.